Penguatan Tata Kelola Koperasi Berbasis Pendampingan di Kabupaten Sukabumi: Integrasi Manajemen Ekuitas, Aset, dan Akuntansi - Sobar, Agus; Ruswandi, Wawan (Penerbit Widina, Widina Media Utama, 2025)
Cooperatives, as business entities that aim to improve the welfare of their members, require good and accountable governance. This community service activity aims to strengthen cooperative governance through the implementation of accounting policies, debt management, and asset management effectively and transparently, as part of a program to strengthen modern and competitive cooperative institutions. The activity was carried out on February 26, 2025, at the Augusta Cicantayan Hotel, Sukabumi Regency, in collaboration with the Sukabumi Regency Cooperative and SME Service as a partner. A total of 25 participants attended, consisting of cooperative administrators, academics, and related service employees. The method used is Participatory Action Research through interactive workshops and mentoring. Field verification to explore real cooperative problems and encourage transparency, accountability, and organizational sustainability. Data analysis is carried out thematically with triangulation of sources and methods to ensure valid and in-depth results. This activity is special because it not only discusses the basic theory of cooperative governance, but also provides a practical approach to managing finances, assets, and accounting records that are rarely discussed in other cooperative training. Collaboration between academics and local governments makes this activity more applicable. As a result, participants understand the material, can prepare simple financial reports, and formulate more structured cooperative policies. This activity provides a real contribution to strengthening modern and accountable cooperative governance.ABSTRAKKoperasi sebagai badan usaha yang bertujuan meningkatkan kesejahteraan anggotanya memerlukan tata kelola yang baik dan akuntabel. Kegiatan pengabdian ini bertujuan memperkuat tata kelola koperasi melalui penerapan kebijakan akuntansi, pengelolaan utang, dan manajemen aset secara efektif dan transparan, sebagai bagian dari program penguatan kelembagaan koperasi modern dan kompetitif. Kegiatan dilaksanakan pada 26 Februari 2025 di Hotel Augusta Cicantayan, Kabupaten Sukabumi, bekerja sama dengan Dinas Koperasi UKM Kabupaten Sukabumi sebagai mitra. Sebanyak 25 peserta hadir, terdiri dari pengurus koperasi, akademisi, dan pegawai dinas terkait. Metode yang digunakan adalah Participatory Action Research melalui workshop interaktif dan pendampingan. Verifikasi lapangan untuk menggali permasalahan nyata koperasi dan mendorong transparansi, akuntabilitas, serta keberlanjutan organisasi. Analisis data dilakukan secara tematik dengan triangulasi sumber dan metode untuk memastikan hasil yang valid dan mendalam. Kegiatan ini istimewa karena tidak hanya membahas teori dasar tata kelola koperasi, tetapi juga memberikan pendekatan praktis dalam mengelola keuangan, aset, dan pencatatan akuntansi yang jarang dibahas dalam pelatihan koperasi lainnya. Kolaborasi antara akademisi dan pemerintah daerah menjadikan kegiatan ini lebih aplikatif. Hasilnya, peserta memahami materi, mampu menyusun laporan keuangan sederhana, dan merumuskan kebijakan koperasi yang lebih tertata. Kegiatan ini memberikan kontribusi nyata dalam memperkuat tata kelola koperasi yang modern dan akuntabel.